A mixed methods study to understand patient expectations for antibiotics for an upper respiratory tract infection. Issue 1 (December 2016) - Gaarslev, Christina; Yee, Melissa; Chan, Georgi; Fletcher-Lartey, Stephanie; Khan, Rabia
Abstract Background Antimicrobial resistance is a public health challenge supplemented by inappropriate prescribing, especially for an upper respiratory tract infection in primary care. Patient/carer expectations have been identified as one of the main drivers for inappropriate antibiotics prescribing by primary care physicians. The aim of this study was to understand who is more likely to expect an antibiotic for an upper respiratory tract infection from their doctor and the reasons underlying it. Methods This study used a sequential mixed methods approach: a nationally representative cross sectional survey (n = 1509) and four focus groups. The outcome of interest was expectation and demand for an antibiotic from a doctor when presenting with a cold or flu. Results The study found 19.5 % of survey respondents reported that they would expect the doctor to prescribe antibiotics for a cold or flu. People younger than 65 years of age, those who never attended university and those speaking a language other than English at home were more likely to expect or demand antibiotics for a cold or flu. People who knew that 'antibiotics don't kill viruses' and agreed that 'taking an antibiotic when one is not needed means they won't work in the future' were less likely to expect or demand antibiotics. The main reasons for expecting antibiotics were believing that antibiotics are an effective treatment for a cold or flu and that they shortened the duration and potential deterioration of their illness. The secondary reason centered around the value or return on investment for visiting a doctor when feeling unwell. Conclusion Our study found that patients do not appear to feel they have a sufficiently strong incentive to consider the impact of their immediate use of antibiotics on antimicrobial resistance. The issue of antibiotic resistance needs to be explained and reframed as a more immediate health issue with dire consequences to ensure the success of future health campaigns.